A, Application Application of Cultural Literacy in Learning in Elementary Schools - Hartinawanti, Hartinawanti; Selvi, Nurhayati (Lembaga Sembilan Tiga Community, 2024)
Cultural literacy is the ability of individuals and societies to act on their social environment as part of culture and state. The increasing flow of information technology greatly affects students' reading interest. The purpose of this study was to explore the application of cultural literacy in SD Negeri 2 Bone-bone. This research is classified as qualitative research with a naturalistic inquiry approach. The subjects involved in this study were the principal, 5 teachers, 10 students and 4 parents. Data collection was carried out using observation and interview methods, with research instruments in the form of observation sheets and interview sheets. Data was analyzed using the Miles and Huberman model, namely data reduction, data display, and conclusion drawing/verification. The results of the research obtained are SD Negeri 2 Bone-bone has implemented cultural literacy by 85% in terms of class base aspects, school cultural aspects, and community base in the form of reading activities ± 15 minutes every day, borrowing books in the library, instilling character values, school literacy facilities and the level of involvement of the facilitator team.